Customized Probability of Vaginal Delivery With Induction of Labor and Expectant Management in Nulliparous Women at 39 Weeks of Gestation. Issue 4 (October 2020) - Silver, Robert M.; Rice, Madeline Murguia; Grobman, William A.; Reddy, Uma M.; Tita, Alan T. N.; Mallett, Gail; Hill, Kim; Thom, Elizabeth A.; El-Sayed, Yasser Y.; Wapner, Ronald J.; Rouse, Dwight J.; Saade, George R.; et al.
Abstract : OBJECTIVE: To develop models to predict vaginal delivery in low-risk, nulliparous women contemplating elective induction of labor or expectant management at 39 weeks of gestation. METHODS: We conducted a secondary analysis of a randomized controlled trial of planned elective induction of labor at 39 weeks of gestation compared with expectant management for low-risk nulliparous women. Two groups were included for this analysis: 1) women who were randomized to the induction of labor group and underwent elective induction at 39 0/7–39 4/7 weeks of gestation and 2) women who were randomized to the expectant management group who experienced spontaneous labor or medically indicated delivery (including postterm). Multivariable logistic regression models were developed for each group using patient characteristics that would be available at the time of counseling. Model selection was based on k-fold cross-validation using backward elimination and variables that remained significant at P <.05 were retained. To compare estimated with observed rates, the elective induction of labor model was then applied to each woman in both groups to estimate individualized predicted probabilities of vaginal delivery with elective induction of labor. RESULTS: Of 6, 106 women enrolled in the trial, 4, 661 met criteria for this analysis. Vaginal delivery occurred in 80.6% of the 2, 153 women in the elective induction of labor group and 77.2% of the 2, 508 women in the expectant management group ( P =.005). The final elective induction of labor model included age, height, weight, and modified Bishop score (area under the receiver operating characteristic curve [AUROC] 0.72, 95% CI 0.70–0.75). The same variables were included in the final expectant management model (AUROC 0.70, 95% CI 0.67–0.72). Across the range of predicted probability deciles derived from the elective induction of labor model, almost all women who underwent elective induction of labor at 39 weeks of gestation had a higher observed chance of vaginal delivery than expectant management. CONCLUSION: Irrespective of the individual predicted chance of vaginal delivery from elective induction of labor at 39 weeks of gestation, vaginal delivery is generally more frequent if elective induction of labor is undertaken rather than expectant management. These data can be used to counsel nulliparous women regarding their "customized" chances of vaginal delivery as they choose between elective induction of labor or expectant management at 39 weeks of gestation. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT01990612. Abstract : Vaginal delivery is more frequent with induction of labor compared with expectant management in low-risk nulliparous women across a range of age, weight, height, and modified Bishop score combinations.